Globalización y relaciones laborales: comparación entre Francia y España. - Costa, Isabel da (Cuadernos de Relaciones Laborales, 2001)
This paper is framed within the theoretical context of the debate on the trend towards the convergence of the various systems of industrial relations linked to economic globalisation. It begins with a brief presentation of the cur rent state of the art, making reference to ideas such as the industrialism» of the 1970s and the theor y of strategic elections of the 1980s and 1990s. By using empirical research on the implementation of Japanese firms in Europe, particularly in France and Spain, it is proven that this does not bring about any equalisation of labour relations. Each countr y maintains, reproduces and rebuilds its own special brand of industrial relations. Not only do institutions and the dynamics of social and labour players count in the practical processes of globalisation, they are active players in its development